2022
DOI: 10.3390/antibiotics11121842
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Analysis of Sulforaphane Anti-Candida Activity

Abstract: Oropharyngeal candidiasis/candidosis is a common and recurrent opportunistic fungal infection. Fluconazole (FLZ), one of the most used and effective antifungal agents, has been associated with a rise of resistant Candida species in immunocompromised patients undergoing prophylactic therapy. Sulforaphane (SFN), a compound from cruciferous vegetables, is an antimicrobial with yet controversial activities and mechanisms on fungi. Herein, the in silico and antifungal activities of SFN against C. albicans were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…Our findings uncovered the significant antibiofilm effect of sulforaphane at sub-MIC, along with its ability to reduce bacterial swarming. These findings are consistent with Silva et al, who demonstrated that sulforaphane had antibiofilm properties against Candida species ( Silva et al, 2022 ) and Streptococcus mutans ( Zhou et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings uncovered the significant antibiofilm effect of sulforaphane at sub-MIC, along with its ability to reduce bacterial swarming. These findings are consistent with Silva et al, who demonstrated that sulforaphane had antibiofilm properties against Candida species ( Silva et al, 2022 ) and Streptococcus mutans ( Zhou et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…Hyphae are important structures of Candida spp. biofilms and are essential for successful fungal colonization and invasion of the host, as the greater the ability of a fungus to adhere to the host, produce hyphae, and form biofilms, the higher the chances of persistent and severe infections [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interesting results indicate the need for further investigations with V. guianensis and its compounds, especially in regards of Candida -induced diseases. Silva and colleagues [ 6 ] assessed the antifungal potential of sulforaphane, an isothiocyanate found in cruciferous plants, with previous suggested antibacterial actions. The authors conducted both in silico analysis and in vitro assays; as expected, in silico analysis confirmed its antimicrobial properties, which include antiparasitic, antifungal, and antibacterial actions, as well as mechanisms ranging from alterations of membrane composition to inhibition of fungi RNA.…”
mentioning
confidence: 99%